The Impact of Climate Change on Livestock Production amongst the Resource-Poor Farmers of Third World Countries: A Review - Musemwa , L; Muchenje , V; Mushunje , A; Zhou , L (Asian Journal of Agriculture and Rural Development, 2012)
The world is currently experiencing average high temperatures and low precipitation, frequent droughts and scarcity of both ground and surface water. The damaging effects of global climate change are increasing and most damages are predicted to occur in developing countries due to their over-reliance on low-input rain-fed agricultural production and their low adaptive capacity. Due to the erratic rainfall and high incidence of droughts which make crop production not feasible, the majority of the rural population in Third World Countries depends on livestock production for their livelihoods. The livestock sector is, however, considered very vulnerable to climate variability and change. Floods, droughts, diseases and poor grazing conditions are some of the factors currently causing significant livestock losses. The problems being encountered by the livestock farmers in most of the Third World Countries are expected to worsen in future due to the effects of climate change. This therefore makes the study of impact of climate change on livestock production a vital concern in the world, particularly in developing countries where many rural households depend on livestock production for their livelihoods. This article therefore looks at both the direct and indirect effects of climate change on livestock production. Strategies to curtail the effect of climate change on livestock production are also recommended in the paper.